Semiconducting polymer composites : principles, morphologies, properties and applications - Yang, Xiaoniu, 1973- (Wiley-VCH, 2012)
"The academic and industrial interest in semiconducting polymer composites is rising, owing to the unique combination of easy and low-cost processability and versatility of these materials. This comprehensive book provides broad coverage addressing the principles of semiconducting polymer blends such as morphology, energetics and processing as well as the wide range of applications in optics, electronics and optoelectronics. Fostering interdisciplinary research, the book combines the fields of polymer composites and functional polymers, allowing for cross-fertilization between these two scientific communities."--anotace vydavatele
Keywords: polovodiče; polymerní kompozitní materiály; semiconductors; polymeric composites; elektronické knihy; electronic books